We are a rainbow - Tabor, Nancy Maria Grande (Watertown, MA : Charlesbridge Publishing, 1997)
"You say sol. I say sun. But no matter how we say it, it is the same one." In WE ARE RAINBOW, the simple comparisons and vivid, cut-paper art who that people of different cultures can have much in common. The message is as universal as it is eloquent: building cultural bridges benefits to everyone.
Keywords: Cultural differences-Juvenile literature